The Violence of Workfare - Jon Burnett (The Violence of Austerity, 2017)
This chapter analyses the testimonies of 97 people who have participated in ‘workfare’ schemes in the UK and have raised concerns about the health and safety risks experienced on these placements. Overall, these placements, which were carried out between May 2011 and November 2015, equate to some 1,139 weeks of compulsory unpaid labour. They were carried out under the threat of having social security benefits removed (sanctioned) if the placements were not completed. Analysing these testimonies, this chapter uncovers 64 concrete allegations of breaches of health and safety legislation at 43 different workplaces. It argues that these placements can constitute a dangerous, and illegal, threat to the safety of benefits claimants. It scrutinises the processes which ensure claimants comply with unsafe working conditions.